Visible-Light-Driven Z-Selective Reaction of Methyl Ketones with DMSO: A Mild Synthetic Approach to Methylthio-Substituted 1,4-Enedione Promoted by Selectfluor™ - Rastogi, Gaurav K.; Deb, Mohit L.; Baruah, Pranjal K. (Synthesis, 2020)
Here we disclose a simple, visible-light-driven Z-selective synthesis of methylthio-substituted 1,4-enedione in a single step promoted by Selectfluor. Dimethyl sulfoxide is used as both the ‘thio’ source and the solvent. Molecular iodine and potassium persulfate are used as catalyst and oxidant, respectively. White light (CFL-30W) is used as the light source. The proposed mechanism involves a Kornblum reaction followed by aldol reaction.
Keywords: visible light; Selectfluor; 1,4-enedione; Z-selective